Stereotip Penduduk Pendatang di Bali: Analisis Framing terhadap Harian Bali Post - Antara, I Putu Juni; Sugiarica Joni, I Dewa Ayu; Pascarani, Ni Nyoman Dewi (E-Jurnal Medium, 2018)
ABSTRACT The issue of migrants is an annual phenomenon which has always been a topic of the news after the Eid. Migrants can be a problem for a region with a high population density such as Bali. These problems can escalate into conflict due to public opinion about migrants. As the largest print media in Bali, Bali Post has a major role in the formation of stereotypes of migrants in Bali. The purpose of this study was to determine the stereotype of migrants formed by the Bali Post. This qualitative study using the constructivist paradigm. The analysis technique used is framing analysis with Pan and Kosicki model. The results showed that the stereotypes of migrants in the Bali Post news tend to be negative, such as slum life, do not obey the administration and tend to work in informal sectors Keywords: framing analysis, Bali Post, migrants, stereotypes